Inflammation as a Key Outcome Pathway in Particle Induced Effects in the Lung - Borm, Paul J. A.; Lison, Dominique; Driscoll, Kevin; Duffin, Rodger; Harkema, Jack; Weber, Klaus; Elder, Alison (Frontiers in Public Health, 2022)
Inflammation is considered a key event in the pathology of many chronic diseases, including pulmonary and systemic particle induced effects. In addition, inflammation is now considered as the key response in standard setting for poorly-soluble low toxicity (PSLT) particles and also the critical endpoint to screen for in OECD based sub-chronic animal inhalation testing protocols. During Particles & Health 2021, an afternoon session was dedicated to the subject and a brief summary of the most important messages are summarized in this paper. In the first part of this session, two speakers (Prof. Lison and Dr Duffin) provided state of the art insight into different aspects and sequels to (persistent) inflammation as a protective or adverse response. Most recent insights on the role of different macrophage cell types were presented as well as perspectives and data provided by inflammatory pathways in humans, such as in asthma and COPD. A brief review of the expert workshop on PSLT particles focusing on the regulatory impact of using persistent inflammation as a key outcome was provided by Kevin Driscoll. The second part of the session focused on the outcomes that are associated with inflammation in animal studies, with an emphasis by Drs. Harkema (Michigan State) and Weber (Anapath) on cell proliferation and other pathologies that need to be considered when comparing human and animal responses, such as outcomes from 14- or 28 day inhalation studies used for specific target organ toxicity classification.